SOLUTIONS TO PROBLEMS IN THE PHARMACEUTICAL INDUSTRY THROUGH MODERN INFORMATION COMMUNICATION TECHNOLOGIES - Kuvatov Jurʼatbek Dilshadbekovich (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The pharmaceutical industry plays a crucial role in advancing global healthcare, but it faces a myriad of challenges that impede progress. From stringent regulatory requirements to complex supply chains and rising R&D costs, the industry is in constant search of innovative solutions. Modern Information Communication Technologies (ICT) emerge as a beacon of hope, offering transformative solutions to age-old problems. In this article, we delve into the ways in which ICT is revolutionizing the pharmaceutical sector.